Analysis of the philosophical foundations of the educational policies in the peruvian State between the years 2011 to 2020 in the dimensions of worldview, epistemology, logic and sociology - Buendía Molina, Marilyn Aurora (2021)
The objective of this research was to analyze the philosophical foundations of educational policy, between the years 2011 to 2020. The methodology used was a systematic review of a documentary, critical-creative and hermeneutical type, for which different sources of information were reviewed that allowed an analysis regarding the available data on educational policy from the governments of former President Ollanta Humala (2011 - 2016), Pedro Pablo Kuczynski (2016 - 2018) to Martin Vizcarra (2018 - 2020). It is concluded that the philosophical foundations used in governments from 2011 to 2020 are focused on the development of the human being as a whole. As the foundations of this study are essential pillars for the development of educational policy in any country, they are also tools that governments have to get involved in the production and distribution of knowledge in a society.